Rights to forests and carbon under REDD+ initiatives in Latin America - Larson, A.M.; Corbera, E.; Cronkleton, P.; Dam, C. van; Bray, D.B.; Estrada, M.; May, P.; Medina, G.; Navarro, G.; Pacheco, P. (Center for International Forestry Research, 2010)
Rights to large areas of forest have been granted to communities and indigenous peoples in Latin America, offering these groups an opportunity to participate in REDD+ initiatives. However, tenure is not always secure, and security of tenure alone is insufficient to guarantee positive outcomes for both forests and livelihoods. The question of carbon tenure rights has only just begun to be addressed, and even less attention has been given to liabilities. REDD+ initiatives provide an opportunity to consolidate indigenous territories but present a risk to those without secure land rights. REDD+ initiatives should be informed by a clear understanding of the successes and failures of community forest management. REDD+ initiatives should recognise local diversity and not impose blueprints.